Discontinuity As Catastrophic Event in Urban Design - Abbas, Sana Sati; Belmessaud, Baya Belmessaud (Iraqi Journal of Architecture and Planning, 2009)
This research is an attempt to study the discontinuity as a catastrophic event in Urban Design, where this phenomenon had been studied in many displines such as Mathematics, Planning , lvedicine ,Surgery and Biology. The research studied this phenomenon from linguistics and conceptual points of views, and submitted its basics in Mathematics according to the Theory of Catasffophe. The research try to borrow this Theory from this field and built a Programme to measure and explore the Discontinuity as a Catastrophic Event in Urban Design. The case study was The fabric surrounded by a new one Casaba of Algeria , rafuch is a traditional urban The research had prepared the axial maps of the Casaba of Algeria for the years (1830,1846,1880,1996,2001), and studied the Relative asymmetry,which was considered as a Behavioral variable affected by two Control variables rvhich were the Connectivity and the Local Control. The research found that there was Bimodality in the behavior of the traditional urban fabric where the Trajectory of balance Manifold moved from segregation to integration by the effect of the new fabric. The research also found that there were two Catastrophic Events happened in the traditional fabric at the years (1830 and 1880) , as a result oflhe unstability of the system ,there types were a Cusp Catastrophe. The Theory of Catastrophe add a new items to the Urban Design such as Singularity, Unstability , and Conflict Nuclei, where the research had proved their appearance in the traditional urban fabric by the effect ofthe new one This research stands as a pioneering attempt in this field.